Predicting naming responses based on pre-articulatory electrical activity in individuals with aphasia. Issue 11 (November 2019) - Wilmskoetter, Janina; Del Gaizo, John; Phillip, Lorelei; Behroozmand, Roozbeh; Gleichgerrcht, Ezequiel; Fridriksson, Julius; Riley, Ellyn; Bonilha, Leonardo
Highlights: Pre-articulatory neural activity can predict correct naming responses in individuals with aphasia. Electrode/time-range/energy combinations with the highest accuracies varied between individuals. Future individualized pre-articulatory models could be used to predict and treat aphasic utterances. Abstract: Objective: To investigate whether pre-articulatory neural activity could be used to predict correct vs. incorrect naming responses in individuals with post-stroke aphasia. Methods: We collected 64-channel high density electroencephalography (hdEEG) data from 5 individuals with chronic post-stroke aphasia (2 female/3 male, median age: 54 years) during naming of 80 concrete images. We applied machine learning on continuous wavelet transformed hdEEG data separately for alpha and beta energy bands (200 ms pre-stimulus to 1500 ms post-stimulus, but before articulation), and determined whether electrode/time-range/energy (ETE) combinations were predictive of correct vs incorrect responses for each participant. Results: The five participants correctly named between 30% and 70% of the 80 stimuli correctly. We observed that pre-articulatory scalp EEG ETE combinations could predict correct vs incorrect responses with accuracies ranging from 63% to 80%. For all but one participant, the prediction accuracies were statistically better than chance. Conclusions: Our findings indicate that pre-articulatory neural activity may be used to predict correct vs incorrect naming responses for some individuals with aphasia. Significance: The individualized pre-articulatory neural pattern associated with correct naming responses could be used to both predict naming problems in aphasia and lead to the development of brain stimulation strategies for treatment.